Effectiveness Of PPPK Orientation Program In Improving PPPK Performance In Wonosobo District - Indah Sri Lestari; Andriyastuti Suratman (International Journal of Economics, Business and Innovation Research, 2025)
PPPK orientation in the State Administration Agency (LAN) Regulation Number 15 of 2020 and LAN Decree Number 289/PDP/K.1/2022 is an activity that aims to provide an understanding and introduction to the duties and functions of ASN, values and ethics, and attitudes to defend the country. The Wonosobo Regency Government through the BKD has implemented a PPPK orientation attended by 318 participants consisting of 293 PPPK formations in 2023, 14 PPPK formations in 2022, and 11 participants in the 2022 formation optimization path. This study uses a descriptive qualitative approach methodology, involving 2 people in charge of PPPK orientation activities, and 1 PPPK orientation participant. Through this study, the author formulates the main problem, namely "How effective is the PPPK orientation program that has been implemented in improving PPPK performance". The results of the study show that the orientation program has an important role in improving PPPK performance. In addition, this study provides recommendations for improving the implementation of orientation in the future, so that it can be more effective in meeting employee needs and improving the quality of superior human resources. Thus, this research is expected to provide a contribution to the Wonosobo Regency BKD in designing better orientation programs.